Impact of digital infrastructure inputs on industrial carbon emission intensity: evidence from China’s manufacturing panel data - Zhang, Wei; Li, Hangyu; Wang, Shaohua; Zhang, Ting (Environmental science and pollution research international, 2023)
Digital infrastructure inputs (DIIs) are vital in strengthening the framework for developing the digital economy and encouraging economic growth. Nonetheless, the risks of environmental contamination are pervasively caused by the rapid expansion and utilization of digital infrastructure. Assessing the carbon emission intensity (CEI) and level of the DIIs of 18 manufacturing in China as the research subject, this study discusses the heterogeneous behavior of various input sources and industries. Furthermore, a two-way fixed effects model, threshold effects model, mediating effects model and moderated mediation effects model have been adopted to examine the nexus between DIIs and CEI of manufacturing. The results show that (1) DIIs raise China’s manufacturing CEI and exert a non-linear threshold effect. (2) From the perspective of national attributes, the foreign DIIs will put more pressure on reducing the CEI in China. From the perspective of industry characteristics, DIIs are the most unfavorable for low-carbon development in capital-intensive industries. (3) Due to the mediating effect of total factor productivity (TFP), the positive influence of DIIs on CEI has dramatically diminished. (4) Participation in the global value chain (PAR) and foreign direct investment (FDI) exert moderating effects in the process of the direct effect and mediating effects. In light of the aforementioned conclusions, specific recommendations for developing digital infrastructure and reducing carbon emissions are proposed.